Constitutional Dimensions of Land Rights in the Era of Climate Change and Food Security: A Transnational Perspective from Indonesia: Constitutional Dimensions of Land Rights in the Era of Climate Change and Food Security: A Transnational Perspective from Indonesia - Astrid Ardhiati; Indah Riyanti; Tubagus Achmad Doradjat (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
Land rights are constitutionally guaranteed in Indonesia, yet their role in addressing global challenges of climate change and food security remains underdeveloped. This study explores the constitutional dimensions of land rights in relation to climate change adaptation and food security, while situating Indonesia within international legal frameworks such as the Paris Agreement, ICESCR, and VGGT. Using a normative juridical method combined with comparative and transnational analysis, the research examines constitutional provisions, agrarian regulations, and relevant international norms. The findings reveal a persistent gap between the normative ideals of Article 33(3) of the 1945 Constitution—which mandates land use for the prosperity of the people—and policy implementation that often prioritizes economic growth over ecological sustainability. Comparative insights from India, Brazil, and South Africa demonstrate how land rights can function as constitutional tools to enhance resilience and food security. By contrast, Indonesia’s fragmented agrarian, food, and climate policies undermine this constitutional potential. This study argues for a reinterpretation of constitutional land rights, shifting from an economic orientation toward a sustainability paradigm. The novelty lies in connecting land rights with the Right to Food and sustainable development, offering theoretical enrichment to constitutional law discourse and practical policy guidance for aligning national agrarian governance with international obligations.